The Role of the Lebanese Mediterranean Diet on Gut Health, Anxiety, and Depression - AbdulGhani, Dana (2022)
Objectives: A Mediterranean-style diet (MeDi) that is rich in high proportion of fibers, healthy fats, antioxidants, and polyphenols has been associated with the prevention of several metabolic diseases. Adherence to the MeDi has been also shown to lower the risk of mental disorders, including anxiety and depression. Several studies have shown that MeDi has been also associated with beneficial changes in gut microbiome composition. The gut microbiome plays an important role in host health and disease. A bacterial imbalance of the gut has been linked to several mental illnesses including anxiety and depression too. The role of gut health on anxiety and depression might be attributed to the effect of the MeDi on gut health. Previous studies have shown that the Lebanese population has low to moderate adherence to MeDi. Furthermore, the effect of this moderate adherence on gut microbiota and on mental health is still missing among Lebanese adults. Therefore, the aim of this study is to examine how adherence to the MeDi affects depression and anxiety via its effect on gut microbiota among Lebanese adults. Methods: This is a pilot cross-sectional study conducted on 75 Lebanese adults aged between 45-65 years recruited from different Lebanese governorates, including Beirut, South Lebanon, and Mount Lebanon. Participants were sent an online invite to our study through different social media platforms (WhatsApp and Instagram), in which information on dietary intake, depression, anxiety, and gut health was collected. Dietary intake was assessed by a 61-item FFQ. Adherence to the Mediterranean diet was calculated by the (Lebanese Mediterranean Diet) LMD index. The gastrointestinal health of the Lebanese adults was evaluated using 9 items of the validated Structured Assessment of Gastrointestinal Symptom (SAGIS) related to the lower GI tract. Depression was assessed using the Patient Health Questionnaire (PHQ-9). Anxiety was assessed using the 7-item tool Generalized Anxiety Disorder (GAD-7). Data were analyzed using STATA version 13. Logistic regression models adjusted for sociodemographic and clinical covariates were used to assess the association between LMD, gut health anxiety, and depression. Results: Among the 68 participants, 48 (70.59%) were females, and the mean age of the whole sample of 55.15 ± 5.5 years. At a logistic regression level, after adjusting for several confounders (age, gender, education, BMI, medications, and physical activity) it has been shown that having high adherence to LMD compared to low adherence were associated with depression (OR=8.16, 95%CI:1.16-57.28, P=0.035). However, high adherence to LMD was not associated with anxiety (OR=0.89,95%CI:0.23-3.4, P=0.866). nor gut health (OR=3.86, 95%CI: 0.78-18.96, p-value: 0.097). Also, scoring more than the mean (>4) for gut health appeared to be associated with depression (OR= 5.64,95%CI: 1.23-25.7, P=0.025) but not with anxiety ([OR= 2.29,95%CI: 0.66-7.93, P=0.188). Conclusion: Our results have shown that a higher LMD adherence was associated with a higher prevalence of depression which is counterintuitive while no significant associations were observed between LMD and anxiety nor gut health. On the other hand, we observed a significant association between gut health and depression with worse gut health was associated with a higher prevalence of depression but not with anxiety. Furthermore, we were not able to demonstrate that LMD would influence depression and anxiety via its mediated effect on gut health ince LMD was not associated with mental health nor associated with gut health. Future longitudinal and randomized studies with a larger sample size are needed to clarify the relationship between LMD, gut health, depression, and anxiety.